Thermal Performance Analysis of Low-GWP Refrigerants in Automotive Air-Conditioning System - Yousuf Alhendal; Abdalla Gomaa; Gamal Bedair; Abdulrahim Kalendar (Advances in Materials Science and Engineering)
The energy and exergy of low-global warming potential (GWP) refrigerants were investigated experimentally and theoretically. Refrigerants with a modest GWP100 of  ≤ 150 can be sufficient for bringing down emissions which were concerned for the automotive air-conditioning system. Three types of low-GWP refrigerants, R152a, R1234yf, and R1234ze(E), were examined with particular reference to the current high-GWP of R134a. The effect of different evaporating and condensing temperatures in addition to compressor speed was considered. The purpose was to bring a clear view of the performance characteristics of possible environment friendly alternatives of R134a. The analysis was carried out with compressor power, cooling capacity, coefficient of performance, exergy destruction, and exergy efficiency. It was noted that the total exergy destruction of R1234yf was reduced by 15% compared to that of R134a. The refrigerant R1234ze(E) has the highest energetic and exergetic performance compared with the other investigated refrigerants.